1983
DOI: 10.1002/ana.410140520
|View full text |Cite
|
Sign up to set email alerts
|

Meperidine‐associated myoclonus and seizures in long‐term hemodialysis patients

Abstract: Kaiko and colleagues [l] are to be congratulated on their clinical investigation of the neuroexcitatory effects of meperidine in cancer patients. Unfortunately, the neurotoxicity associated with this drug is not well appreciated in the medical community, as is illustrated by the following cases of neurotoxicity in two patients with chronic renal failure who were on hemodialysis. To my knowledge, only a single renal failure patient with such neurotoxiciry has been previously reported [2].A 61-year-old man had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…A prerequisite is, however, that polar metabolites of such drugs are pharmacologically inactive since they will tend to accumulate in uraemia. An example is pethidine whose metabolite norpethidine is slowly eliminated in uraemic patients and which is probably responsible for convulsions sometimes seen in this group of patients (Szeto et al, 1977;Hochman, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A prerequisite is, however, that polar metabolites of such drugs are pharmacologically inactive since they will tend to accumulate in uraemia. An example is pethidine whose metabolite norpethidine is slowly eliminated in uraemic patients and which is probably responsible for convulsions sometimes seen in this group of patients (Szeto et al, 1977;Hochman, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of precipitating convulsions is theoretically greater with chronic oral administration because it produces lower meperidine and higher normeperidine blood levels due to extensive firstpass metabolism (102). However, seizures have occurred after both chronic oral (99,103) and intramuscular (100,104) administration. Myoclonus generally precedes the seizures, and both resolve over several days with discontinuation of meperidine administration (101,103).…”
Section: Intravenous Analgesics Opioid (Narcotic) Analgesicsmentioning
confidence: 99%
“…However, seizures have occurred after both chronic oral (99,103) and intramuscular (100,104) administration. Myoclonus generally precedes the seizures, and both resolve over several days with discontinuation of meperidine administration (101,103).…”
Section: Intravenous Analgesics Opioid (Narcotic) Analgesicsmentioning
confidence: 99%
“…Ten of the 50 reported patients (20%) had renal impairment, and 3/50 patients (6%) had liver impairment. Other confounding conditions included alcohol abuse (Danziger et al, 1994;Marinella, 1997), infection (Rodman and Maxwell, 1994;Knight et al, 2000;Hubbard and Wolfe, 2003;Eker et al, 2009), prior seizure history (Hochman, 1983;Stone et al, 1993), sickle cell disease (Pryle et al, 1992;Hagmeyer et al, 1993;Liu et al, 1994;Rodman and Maxwell, 1994;Nadvi et al, 1999;Dunwoody et al, 2006), and malignancy (Szeto et al, 1977;Kaiko et al, 1983;Armstrong and Bersten, 1986). One patient had Alzheimer's disease (Nagler et al, 2008), one had hereditary coproporphyria (Deeg and Rajamani, 1990), and one had severe burns and hyponatremia (Kyff and Rice, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we found that clinical evidence relating meperidine use to seizures is scant overall, emphasizing the weakness of this association. Literature reports of seizures due to meperidine are confounded by use of other medications with potentially epileptogenic potential (Rodman and Maxwell, 1994), malignancy (Szeto et al, 1977;Kaiko et al, 1983;Armstrong and Bersten, 1986), renal impairment (Kaiko et al, 1983;Adair and Gilmore, 1994), prior seizures (Hochman, 1983), and sickling diseases (Pryle et al, 1992;Hagmeyer et al, 1993;Liu et al, 1994;Rodman and Maxwell, 1994;Nadvi et al, 1999;Dunwoody et al, 2006). The cases we reviewed included a significant number of pediatric patients (12/50 patients; age range 15 days to 17 years) in whom the metabolism and elimination of meperidine are lower (Pokela et al, 1992).…”
Section: Discussionmentioning
confidence: 99%